2018
DOI: 10.31449/inf.v42i4.1571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Systems: A Visual Survey

Abstract: Clinical Decision Support Systems (CDSS) form an important area of research. In spite of its importance, it is difficult for researchers to evaluate the domain primarily because of a considerable spread of relevant literature in interdisciplinary domains. Previous surveys of CDSS have examined the domain from the perspective of individual disciplines. However, to the best of our knowledge, no visual scientometric survey of CDSS has previously been conducted which provides a broader spectrum of the domain with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Several studies have pointed to the role of various CDSSs in reducing drug errors. 10,24,[35][36][37][38] Especially, CPOE coupled with CDSS has been able to significantly reduce therapeutic medication errors based on the rules derived from the therapeutic protocols. 26,[38][39][40][41] The results of this study on alert cases deviating from the chemotherapy protocol by CPDSS showed that this system could help find chemotherapy drug errors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed to the role of various CDSSs in reducing drug errors. 10,24,[35][36][37][38] Especially, CPOE coupled with CDSS has been able to significantly reduce therapeutic medication errors based on the rules derived from the therapeutic protocols. 26,[38][39][40][41] The results of this study on alert cases deviating from the chemotherapy protocol by CPDSS showed that this system could help find chemotherapy drug errors.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is significantly impacting on receiving regular medication, and patients should thus get it. While patients with eating disorders are identified, they also get dietary guidance to help them develop appropriate treatment plans [107]. As a further point, there are so many challenges that occur during the diagnosis of GC.…”
Section: Incorporated Into the Healthcare Sectormentioning
confidence: 99%
“…Research method for bibliographic analysis of Marketing research adopted from(Farooq, Khan, Niazi, Leslie, & Hussain, 2018) …”
mentioning
confidence: 99%